A Low-Power, Ambiguous Synthetic Aperture Radar Concept for Continuous Ship Monitoring - Ustalli, Nertjana; Krieger, Gerhard; Villano, Michelangelo (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2022)
This article addresses the design of a low-cost synthetic aperture radar (SAR) for a single dedicated application, namely illegal vessel detection, which can be implemented using a small satellite and is characterized by reduced transmit power and high resolution. Minimum requirements in terms of noise equivalent sigma zero and resolution that ensure acceptable detection performance are derived on the basis of ship statistics extracted from TerraSAR-X data. One peculiarity of the design is that a pulse repetition frequency much smaller than the nominal Doppler bandwidth is selected to increase the swath width beyond the classical SAR limitation without using digital beamforming, as the azimuth ambiguities can be tolerated for this specific application. Several design examples of SAR systems operating in x-band demonstrate the potential of this concept for small ship monitoring over swaths of 50–90 km with antennas smaller than 0.6 m2: and very low average transmit powers comprised between 20 and 80 W.
Created from Fastlane, Scopus look-up
Keywords: Azimuth; Clutter; Marine vehicles; Radar polarimetry; Small satellites; Standards; Synthetic aperture radar